(untitled) (Scientific journal of the Fergana State University, 2026)
This article provides detailed information about the essence, formation and role of mass culture in society. The article analyzes various forms of mass culture, its widespread distribution through mass communication media such as music, cinema, television, the Internet and advertising. It also discusses the negative effects of mass culture. In general, the article examines the multifaceted role of mass culture in society and the lives of young people, as well as its negative and positive aspects.